The Estimation of Bioethanol Yield From Some Cassava Variety - M.C. Tri Atmodjo (Bandar Lampung University (UBL), 2013)
In this research was examined several variety of cassava which were , UJ-3, Kaserstaat, Caspro, and Malang 6 as the raw materials of bioethanol. The result of the fermentation that the bioethanol content along 72 hours of fermentation process showed different concentration of green energy bioethnol between UJ-3 , Kaserstaat, Malang -6 and Caspro respectively There are many variety of cassava which are able to use as the raw materials of Green Energy Bioethanol. One litre of Green Energy Bioethanol usualy needs 6 kg until 7 kg of cassava as the raw materials. The Total Sugar content of cassava, will influence the amount of cassava as the raw material for bioethanol . Sacharification process is one step of Bioethanol production will continue by fermentation process along 72 hours. The higest starch content of cassava lines got the highest concentration green energy bioethanol. The lowest starch content of cassava lines got the lowest concentration of green energy bioethanol. In this research showed that the first grade and the second grade in producing bioethanol are Kaserstaat and Caspro respectively. There are different concentration of bioethanol in each cassava lines along 72 hours of inoculation.